(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2024)
An information system for asset management in a university is very important, especially in a faculty with many majors. There are a lot of assets, including laboratories and items inside. In this research, the authors present the development of an information system using feature-driven development (FDD) methodology, which is one of the agile methods, giving flexible and collaborative methods prioritizing main users. To communicate between stakeholders, the development of initial models using UML diagrams, such as use case diagrams, sequence diagrams, and deployment diagrams. The modules on this asset management website are administration for building and room data, asset categorization, asset search, and asset maintenance and problem reporting. The website was developed using PHP with a Laravel framework and MySQL database. This website is beneficial for increasing the efficiency of assets, with future development involving more advanced technology.